Peculiarities of the Provision of Surgical Care for Abdominal Emergencies in Hospitals Remodeled to Provide Medical Care to Patients with COVID-19 From the Perspective of a Systematic Review and Analysis of the Quality of Publications - A. M. Karsanov; V. V. Aleksandrov; S. S. Maskin; A. Ya. Korovin; K. I. Popandopulo (Неотложная медицинская помощь)
Relevance. Due to the pandemic of the new coronavirus infection, changes have occurred in the work of most surgical hospitals aimed at optimizing and improving the provision of medical care. Performing acute and emergency surgical interventions in patients with confirmed COVID-19 infection dictates the need to review surgical tactics.Aim of study. To assess the quality of publications in the scientific press from the standpoint of systematic analysis on the provision of emergency surgical care in remodeled hospitals and to identify the main changes in surgical tactics in patients with abdominal emergency and COVID-19.Material and Methods. The analysis of data from publications dated from December 2019 to July 10, 2021 from electronic databases PubMed, Cochrane Library, Scopus, eLibrary. An analysis of numerous studies, recommendations of national and international surgical, urological, oncological, gynecological, endoscopic and anesthesiological communities and associations, the World Health Organization, temporary guidelines of the Ministry of Health of the Russian Federation on the prevention, diagnosis and treatment of new coronavirus infection was performed. The quality of the selected publications was assessed in accordance with the recommendations.Results. When analyzing the selected publications, it was revealed that most of them are retrospective, uncontrolled one-time studies and descriptions of clinical cases (level 4 evidence, level C recommendation). We found 1 combined (prospective-retrospective) multicenter and 1 retrospective comparative study on the treatment tactics of acute cholecystitis, 1 retrospective multicenter cohort study on acute pancreatitis, 1 retrospective study on acute intestinal obstruction and 2 studies on acute appendicitis, 1 case-control study on gastrointestinal tract and intestinal bleeding (level 3 evidence, level B recommendation).Conclusion. Currently, there are no high-level evidence or recommendations to change surgical tactics in patients with COVID-19 and abdominal emergency.